Perbandingan Analisis Keputusan dalam Penentuan Lokasi Gudang Angkatan Laut Wilayah Barat - Oktavia, Chendrasari Wahyu; Natalia, Christine; Ratanadewi, Steffi; Gunawan, Sherly (Metris: Jurnal Sains dan Teknologi, 2018)
The development of a company is always related to its supporting facilities’ location, for instance, warehouse location. Usually, company choose the most strategic one to minimize its transportation cost, distribution route and time. As the result, it is clear that warehouse location determination is the key to company’s success in delivering consumer needs. Location determination is not only used in manufacturing problem, but it is also can be used in national defense problem, which is the case study of this research: Western Sea Sector Indonesian Navy. In national defense, national and regional development are important factors for maximizing Indonesian Navy’s strength. As an example, logistics capability improvement. Logistics is one of the most important parts to support warships in doing their maritime operations. So, strategy of determinating the best warehouse location is very crucial to make sure the distribution of goods went smoothly. This research uses Multi Criteria Decision Making (MCDM) as a method to solve location determination problem. Using a study case from main literature by Gunawan et al (2018), this research does another two methods for problem solving, they are Fuzzy Simple Additive Weighting (F-SAW) and Fuzzy Analytical Hierarchy Process (F-AHP). The main purpose of this research is to compare Fuzzy MCDM method, which is used by Gunawan et al (2018), with F-SAW and F-AHP which is calculated in this research. Result shows that Naval Base III is the best location from Fuzzy MCDM and F-AHP, but the best location from F-SAW method is Naval Base I.